ANALISIS DAN PERANCANGAN KNOWLEDGE MANAGEMENT SYSTEM UNTUK MENINGKATKAN KINERJA PEGAWAI PADA BADAN NARKOTIKA NASIONAL KOTA TANGERANG SELATAN BERBASIS WEBISTE - Rosalina Aprianti; Yuni Sugiarti (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2022)
Technology is growing nowadays, so that organizations must keep up with existing technological developments as well as the National Narcotics Agency for South Tangerang City (BNN South Tangerang City) to manage knowledge which is an organizational asset, a knowledge management system is needed. The purpose of this research is to produce a knowledge management system design that can employees use to document and share knowledge. Data collection methods used are observation, interviews, and literature study. The system development method used is Rapid Application Development (RAD) and uses Unified Modeling Language (UML) as a tool for describing and designing the system. The result of this research is a knowledge management system that can help employees to acquire knowledge effectively and efficiently.